ZAMZAM MART MINI MARKET BUSINESS STRATEGIES WITH CUSTOMER SURVEY AND BMC ANALYSIS - Ahmad, Zahid; Sutopo, Sutopo; Solehudin, Tohir (Al-Infaq: Jurnal Ekonomi Islam, 2024)
A mini market is a small store that sells various goods and food, similar to a supermarket but on a smaller scale. The presence of Zamzam Mart as a mini market run by selfemployed entrepreneurs in the Ciampea Udik region of Bogor is crucial and provides convenience for rural residents who are not accustomed to online shopping. However, the competition with franchise businesses is intense. The research aims to develop strategies to enhance Zamzam Mart's competitiveness through customer surveys. The research method involves creating a survey questionnaire with 7 questions rated on a 5-point scale, conducting surveys and data analysis, with the respondents being local consumers. The Business Model Canvas (BMC) is then analyzed. The response rate was 71% (71 out of100 questionnaires). The respondents included children (7%), adolescents (34%), young adults (14%), male adults (11%), and female adults (34%), with the highest frequency of visits being twice a week (48.3%). The survey results revealed that 47.8% of respondents rated the product prices as "good," while 39.4% rated the product variety as "good." Additionally, 45% were satisfied with the variety of goods, 49.2% with the service, and 40.8% rated the hygiene as "very good." Products that were not available but needed by consumers included items for specific uses such as baby products, cosmetics, and office supplies, with 47.9% of respondents expressing the need for these product categories to be stocked. The BMC analysis identified the need to improve relationships with suppliers,customers, and major activities.